The Use of Podcast to Teach Listening Comprehension to EFL Students: A Library Research - Entin Novianty; Eusabinus Bunau; Wardah (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research provides a review of the current literature on podcast in listening comprehension of EFL students. The type of research is library research study. The aim of this research is to analyze the effect of podcast in improving listening comprehension skills on EFL students. This paper reviewed six articles conducted between 2010-2020 utilizing multiple databases, they are ProQuest, EBSCOhost, and Springer Link through the digital library e- resource Perpustakaan Nasional RI. Furthermore, Google Scholar and Research Gate were used as additional resources. Each relevant publication screened according to some parameters; year of publishing, country, research purpose, research participant, methodology, research finding, type of article, and article in English text. A preliminary synthesis indicates that the majority of studies related to podcasts in improving listening comprehension to EFL students focused on the themes namely: (1) the effect of listening to podcast in improving students’ listening comprehension and (2) how podcast improve students’ positive perception and satisfiction in learning, then finally affected the improvement of students’ listening comprehension skills. A number of suggestions for future research have emerged from the quality and the content of previous studies. They are methodology and quality design of podcast to determine the long-term effects of podcasting on learning outcomes.